The Trouble With Quantifiers: Exploring Children's Deficits in Scalar Implicature. Issue 6 (29th December 2017) - Horowitz, Alexandra C.; Schneider, Rose M.; Frank, Michael C.
Abstract : Adults routinely use the context of utterances to infer a meaning beyond the literal semantics of their words (e.g., inferring from "She ate some of the cookies" that she ate some, but not all). Contrasting children's ( N  = 209) comprehension of scalar implicatures using quantifiers with contextually derived ad hoc implicatures revealed that 4‐ to 5‐year‐olds reliably computed ad hoc, but not scalar, implicatures (Experiment 1). Unexpectedly, performance with "some" and "none" was correlated (Experiments 1 and 2). An individual differences study revealed a correlation between quantifier knowledge and implicature success (Experiment 3); a control study ruled out other factors (Experiment 4). These findings suggest that some failures with scalar implicatures may be rooted in a lack of semantic knowledge rather than general pragmatic or processing demands.